Lactose malabsorption based on breath hydrogen test in children with recurrent abdominal pain - Elizabeth Yohmi; Aswitha D Boediarso; Sri Rezeki S Hadinegoro (Indonesian Pediatric Society Publishing House, 2016)
Background Recurrent abdominal pain (RAP) is common among school-age children. Previous studies found that lactose malab- sorption has an important role in RAP in children. Up to date, data on the prevalence of lactose malabsorption in children with RAP in Indonesia has not been available. Objective To elicit the prevalence of RAP and lactose malabsorption in children with RAP, and to determine associated foods that cause RAP in children with and without lactose malabsorption, the frequency of lactose intolerance during breath hydrogen test (BHT), and also the onset and duration of the symptoms after a lactose load. Methods This was a cross-sectional study conducted on junior high school students who suffered from recurrent abdominal pain. Results Of 1054 students screened, 157 (14.9%) fulfilled the Apley's criteria for RAP. Of 157, 85 children were enrolled and underwent BHT. Fifty five of them (65%) were girls. Lactose malabsorption was found in 68 (80%) subjects. Milk and yogurt were the most frequent products that cause symptoms of RAP in our subjects who mostly (80%) were malabsorber. Lactose intolerance during BHT was found in 69 (81%) children. Symptoms appeared in 30 minutes after lactose ingestion, and the most frequent symptom was abdominal pain (44%). Lactose intolerance symptoms disap- peared in about 15 hours. Conclusions The prevalence of RAP in children aged 12-14 years was 14.9%. The prevalence of lactose malabsorption in children with RAP was 80%. Milk and yogurt were the most frequent products that cause symptoms of RAP in our subjects who mostly were malabsorbers. The frequency of lactose intolerance during BHT was 81%, and the symptoms lasted within approximately 15 hours